TOTAL PLATE NUMBERS TEST (ALT) ON BOILED MACKAREL TUNA (Euthynnus affinis) TO THE DIFFERENT BOILING TIME WITH THE POUR PLATE METHOD - Apri Mujiyanti; Nirmala Efri Hasibuan; Bayythi Jaynaythi (Politeknik Kelautan dan Perikanan Dumai, 2021)
Pindang mackarel tuna/ boiled mackarel tuna (Euthynnus affinis) is a traditional fishery product that contains nutrients in the form of protein, fat, vitamins and minerals needed by the body, but on the other hand it is easy to quality deterioration, this is because it have high protein content with amino acid content. which is used for the metabolism of microorganisms and the production of ammonia. To identify the quality of fish, microbiological testing can be carried out in the laboratory, namely by testing the Total Plate Number (ALT). This test is a quality parameter in fishery products. The method used in the ALT test is the pour plate method with boiling time treatment of 1 hour, 2 hours, and 3 hours. The results of the total microbial analysis of boiled mackarel tuna at 3 hours boiling time obtained ALT value of 0.047 x 103 CFU / gram, this shows that the boiling time will be inversely proportional to the number of microbes contained in boiled mackarel tuna.